Pertanggungjaawaban Pidana Pelaku Tindak Pidana Penggelapan (Analisis Putusan Pengadilan Negeri Bekasi Nomor 120/Pid.B/2019/PN.Bks) - Chrysta Kusuma; Ardison Asri (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
The crime of embezzlement is regulated in Book Two of the Criminal Code, Chapter XXIV, Articles 372 to Article 377 of the Criminal Code. Embezzlement in all its forms is a type of criminal act that is quite serious when viewed from the consequences it causes and its influence on society. Embezzlement is a crime against property. Therefore, it is interesting to examine how the criminal act of embezzlement is regulated in Indonesian criminal law and the decision of the Panel of Judges in the Bekasi District Court Decision Number 120/Pid.B/2019/PN.Bks., Concerning the Criminal Liability of Perpetrators of the Crime of Embezzlement Has Fulfilled the Elements of Justice. To answer these problems, normative legal research methods (normative juridical) are used with a statutory approach, case approach and conceptual approach, using secondary data obtained from primary, secondary and tertiary legal material sources. The research found that the regulation of the criminal act of embezzlement in Indonesian criminal law is a criminal act originating from German law. The words unterslagung or verduistering (embezzlement) by the founders of the Dutch Wetboek van Strafrecht are regulated in Article 321 WvS whose formulation is the same as Article 372 of the Criminal Code and the decision of the panel of judges regarding the criminal liability of perpetrators of embezzlement crimes is appropriate. regarding the subject matter of the case, or for a criminal act charged by the public prosecutor where in the decision of this case the defendant was sentenced to a sentence because he was legally and convincingly proven to have committed the crime of embezzlement as intended by Article 372 of the Criminal Code and fulfilled the elements of justice because it was based on 2 (two) additional pieces of evidence. judge's belief (Article 183 of the Criminal Procedure Code). Be careful and research and see the truth of the information and there are legal appeals from the prosecutor, in order to achieve a sense of justice.